Determinan Kualitas Laporan Keuangan Kota Palembang - Sri Rahayuningsih; Maria Maria; Darul Amri (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study is intended to determine the contribution of the Internal Control System (SPI), Regional Financial Accounting System (SAKD), and the use of information technology (TI) to the quality of financial reports in the Palembang city government. The study was conducted at the Regional Financial and Asset Management Agency (BPKAD) of Palembang city as a reporting entity involving 65 employees as respondents. Respondents consisted of employees in the field of accounting, regional maintenance, asset management and regional budget fields. Sampling using saturated samples. The findings show that the quality of financial reporting is influenced by the application of SPI, SAKD, and IT by 93.9%. These three factors also have an impact on the reliability of financial statements. Keywords: SPI , SAKD, information technology, Financial Statements